A formação continuada de professores em parceria com os gestores: relações andragógicas - Silva, Fábio Anderson de Assumpção (2023)
Whenever there is talk of continuing teacher education, school management and teachers commonly direct their perspectives to pedagogical training; the use of new information and communication technologies and the resumption of disciplinary content, leaving aside interactions, integrations, socializations, exchanges of experiences and so many other actions that are essential for learning among adults. Thus, this work aims to present the concepts of teacher training and school management, defended by Masetto (2018), Libâneo (2012), Imbernóm (2010), Feuerstein (1990) and Luck (2010), among others, and integrate them with Andragogy, which according to Knowles (2009), is a science that studies adult education. To carry out, this research work qualitative research is chosen, starting with research-training, passing through bibliographic research and ending with the documental analysis of the training guidelines of the meetings of continuing teacher training in a school unit in the city of São Paulo. After the research, it was found that Andragogy favors the partnership between managers and teachers in the construction of a participatory, collaborative and significant work of continuing teacher education